A Platform for Multimedia Traffic Forwarding in Software Defined Networks - Diorio, Rafael Fernando; Timóteo, Varese Salvador (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2015: Proceedings of the 21st Brazilian Symposium on Multimedia and the Web, 2015)
This paper presents a platform for multimedia traffic forwarding in OpenFlow Software Defined Networks (SDN). Its functional structure, developed as an extension to OpenFlow controller, uses a selective packet forwarding mechanism, QoS mechanism and multimedia cache mechanism to enable its operation. Preliminary results demonstrate that the proposed platform can be used in SDN environments, enabling selective packet forwarding and providing QoS and cache resources for multimedia traffic flows.